A Texture Fuzzy Classifier Based on the Training Set Clustering by a Self-Organizing Neural Network; Communications in Computer and Information Science; Vol. 542 : Analysis of Images, Social Networks and Texts - Aksenov S. V. Sergey Vladimirovich (2015, 2015)
Title screen